2021
DOI: 10.1136/emermed-2020-210401
|View full text |Cite
|
Sign up to set email alerts
|

Usability of electronic health record systems in UK EDs

Abstract: BackgroundThe large volume of patients, rapid staff turnover and high work pressure mean that the usability of all systems within the ED is important. The transition to electronic health records (EHRs) has brought many benefits to emergency care but imposes a significant burden on staff to enter data. Poor usability has a direct consequence and opportunity cost in staff time and resources that could otherwise be employed in patient care. This research measures the usability of EHR systems in UK EDs using a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…These results concur with the other studies which have shown that clinical decision support system usability quality was good [10][11][12]. In contrast to some reports in the literature, there was usability quality of clinical information systems was low [7,13]. This study indirectly implies that end-user involvement in the design of clinical decision support systems and homegrown clinical information systems improves the success and adoption rate of these systems.…”
Section: Discussionsupporting
confidence: 88%
“…These results concur with the other studies which have shown that clinical decision support system usability quality was good [10][11][12]. In contrast to some reports in the literature, there was usability quality of clinical information systems was low [7,13]. This study indirectly implies that end-user involvement in the design of clinical decision support systems and homegrown clinical information systems improves the success and adoption rate of these systems.…”
Section: Discussionsupporting
confidence: 88%
“…The tool has been used to assess the usability of, cell phones, appliances such as TV and microwaves and websites [42]. Recently, SUS has been utilized in healthcare to evaluate the usability of internet-based healthcare interventions used by professionals, electronic health records, home healthcare devices, mobile health applications, and electronic medication adherence products [43][44][45][46][47].…”
Section: System Usability Scalementioning
confidence: 99%
“…Finally, we must remember that the infrastructure for creating, storing, processing, and transmitting health and care data, while sometimes invisible, has environmental and human costs 19. Just as extracting the raw materials for technology manufacture requires miners to work in unpleasant and sometimes unsafe conditions, the production of healthcare data is often associated with clinician burnout20 and cognitive overload21 related to poor system design22 and usability 23…”
Section: Learning Systemmentioning
confidence: 99%